2011
DOI: 10.1371/journal.pone.0018605
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulatory Gαs Protein Is Involved in Olfactory Signal Transduction in Drosophila

Abstract: Seven-transmembrane receptors typically mediate olfactory signal transduction by coupling to G-proteins. Although insect odorant receptors have seven transmembrane domains like G-protein coupled receptors, they have an inverted membrane topology, constituting a key difference between the olfactory systems of insects and other animals. While heteromeric insect ORs form ligand-activated non-selective cation channels in recombinant expression systems, the evidence for an involvement of cyclic nucleotides and G-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 81 publications
2
58
0
1
Order By: Relevance
“…However, little is known about the molecular basis for this sensitivity. Studies have shown that the OrX-Orco complex is subject to metabotropic signalling (Stengl, 1993(Stengl, , 2010Kain et al, 2008;Wicher et al, 2008;Deng et al, 2011;Sargsyan et al, 2011;Getahun et al, 2013;Ignatious Raja et al, 2014;Carraher et al, 2015) and also that OrX-Orco activation enhances secondary messenger production (Wicher, et al, 2008;Miazzi et al, 2016). Neither OrX nor Orco has any obvious homology to known cyclic nucleotide binding domains, and it is not clear how these two proteins interact.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the molecular basis for this sensitivity. Studies have shown that the OrX-Orco complex is subject to metabotropic signalling (Stengl, 1993(Stengl, , 2010Kain et al, 2008;Wicher et al, 2008;Deng et al, 2011;Sargsyan et al, 2011;Getahun et al, 2013;Ignatious Raja et al, 2014;Carraher et al, 2015) and also that OrX-Orco activation enhances secondary messenger production (Wicher, et al, 2008;Miazzi et al, 2016). Neither OrX nor Orco has any obvious homology to known cyclic nucleotide binding domains, and it is not clear how these two proteins interact.…”
Section: Introductionmentioning
confidence: 99%
“…The second messenger 3′,5′-cyclic adenosine monophosphate (cAMP) is an activating ligand for Orco channels (Wicher et al, 2008;Stengl, 2010;Stengl and Funk, 2013) and has been shown to enhance the activity of olfactory sensory neurons (OSNs) that express ORs (Olsson et al, 2011;Getahun et al, 2013). Insect OSNs possess the cellular machinery required to produce cAMP (Iourgenko and Levin, 2000;Boto et al, 2010) and disruption of this signaling cascade has been reported to affect the functional properties of OSNs (Martín et al, 2001;Gomez-Diaz et al, 2004;Deng et al, 2011). However, insect ORs show an inverted topology with respect to their mammalian counterparts (Benton et al, 2006), they are not related to any known G protein-coupled receptor and there is no proof of a direct interaction between insect ORs and G proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been used to study the effect of cAMP on OR modulation, including genetic manipulations coupled with electrophysiological (Martín et al, 2001;Deng et al, 2011), behavioral (Martín et al, 2001Gomez-Diaz et al, 2004) and optogenetic (Bellmann et al, 2010) experiments. The recent establishment of genetically encoded cAMP fluorescent indicators has broadened the number of possible approaches (Gorshkov and Zhang, 2014;Calebiro and Maiellaro, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this 'chaperone-like function', Orco forms a non-specific, spontaneously opening Ca 2+ -permeable cation channel in heterologous expression systems (Sato et al, 2008;Wicher et al, 2008;Jones et al, 2011;Sargsyan et al, 2011;Nolte et al, 2013). Because ORNs in Orco-mutant flies showed strongly diminished spontaneous action potential activity, Orco controls the membrane potential and, thus, the spontaneous activity of ORNs as a prominent leak channel (Larsson et al, 2004;Benton et al, 2007;Deng et al, 2011). Orco's property as a leaky ion channel controlling spontaneous membrane potential oscillations was previously termed the 'pacemaker channel function' to distinguish it from the 'chaperone function' of Orco (Stengl, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As only coexpression of MsexOrco with MsexOr1 but not with MsexOr4 conferred BAL sensitivity, MsexOr1 is the BAL-ligand binding subunit. Because it was very difficult to obtain any plasma membrane expression of any of the subunits tested, it was not examined whether MsexOr1 expression alone is sufficient to elicit BAL responses, as was found for OrX proteins from other species (Wetzel et al, 2001;Sakurai et al, 2004;Nakagawa et al, 2005;Neuhaus et al, 2005;Grosse-Wilde et al, 2006;Smart et al, 2008;Deng et al, 2011). It still remains unknown whether MsexOr4 would detect minor components of the M. sexta pheromone blend.…”
mentioning
confidence: 99%